THE INFLUENCE OF ADVERTISING AND PRODUCT DIVERSITY ON CONSUMER PURCHASE INTENTION OF AICE ICE CREAM PRODUCTS (on Students of State Polytechnic of Malang) - Kharisma Lia Widia Tama; Arni Utamaningsih; Yosi Afandi (Manajemen Bisnis, 2025)
The increasingly intense business competitions demands companies are more creative in developing their business. Advertising and product diversity are key factors that companies must consider. Aice ice cream utilizes Instagram as its advertising platform, however from August to December 2024 there was a noticeable decline in both viewers and likes on its content, and its product diversity remains inferior compared to competitors. This study aims to examine and analyze the influence of advertising and product diversity on consumer purchase intention. This research employed a quantitative approach. The data collection method employed an online questionnaire distributed to 100 respondents, specifically students of State Polytechnic of Malang, utilizing simple random sampling techniques. The data were analyzed using multiple linear regression and hypothesis testing. The findings of the current study demonstrated that both advertising and product diversity had a positive and significant impact on purchase intention. Therefore, Aice should maintain and enhance the quality of its advertising and product diversity to further increase consumer purchase intention.